Interdigitated capacitor incorporating chitosan film as mercury metal ion sensor at microwave frequency - Radzali, Rashidah (2016)
Various techniques have been used to determine the presence of heavy metal ion. This thesis propose a new finding in a detection of heavy metal ion focusing on mercury metal ion which is by using Interdigitated Capacitor (IDC) and chitosan film as sensor at microwave frequency. This method was chosen because the existing methods to determine the presence of heavy metal ion are complicated and time consuming. IDC sensor incorporating chitosan film will be a novel method as it has never been used to determine the presence of heavy metal ion. The simplicity and cost effective of this project will be a good finding to detect mercury metal ion as well as iron and lead ions. Resistivity measurement of chitosan film dipped into mercury solution with different temperatures, concentrations and contact time were carried out by using Four-Point Probe. Resistivity of chitosan film increased with increasing concentration and contact time of mercury solution and decreased with increasing temperature. This measurement shows the capability of chitosan to detect the presence of mercury ion by changing in value of resistivity. IDC sensor was designed and fabricated at frequency range between 130 MHz to 3 GHz. For the microwave measurement, in order to make sure IDC sensor functioning well, the test result for the IDC sensor had been carried out. It shows good agreement with the simulation result and the best sensor has been chosen for microwave measurement. IDC sensor was then combine with chitosan film and tested for capacitance and transmission (S21) measurement. Chitosan film was dipped into different concentrations of heavy metal ions which are mercury (Hg), lead (Pb) and Iron (Fe). Results show the capacitance increased with increasing concentration for mercury, iron and lead solution. Transmission (S21) measurement was only carried out for mercury solution and it increased with concentration of mercury solution. Based on the result, this research has proved the capability of IDC sensor incorporating chitosan film to detect the presence of heavy metal ion at 1 ppm to 10 ppm by changing in value of capacitance as well as transmission (S21).